Accelerated galvanic interaction for the fabrication of core-shell nanowires to boost the hydrogen evolution reaction - Yang, Zhongyun; Zhang, Xiaojia; Yang, Fan; Waqas, Muhammad; Peng, Yufeng; Wang, Limin; Huang, Qiulan; Huang, Dujuan; Deng, Dingrong; Chen, Du-Hong; Fan, Youjun; Chen, Wei (Nanoscale, 2025)
As an essential reaction of water splitting in alkaline solution, the hydrogen evolution reaction (HER) is seriously limited by its ponderous dynamics and the dissolution of Ru. Herein, we propose a strategy for the electrochemical deposition of Ru nanoparticles on the surface of Ag nanowires (Ag NWs) to generate a core-shell Ru@Ag/AgCl catalyst through an accelerated galvanostatic interaction conducted in RuCl 3 solution. The active sites of Ru were precisely controlled by tailoring the number of cycles in cyclic voltammetry (CV). Interestingly, the as-designed Ru@Ag/AgCl-200 electrode maintained its original morphology after 200 CV cycles, demonstrating the high stability of the designed electrocatalyst. The electrochemical performance of the Ru@Ag/AgCl-200 catalyst justifies its excellent HER performance, including a low overpotential of 40.2 mV at a current density of 10 mA cm −2 , small Tafel slope of 53.24 mV dec −1 , and great stability, compared to other control catalysts. Furthermore, the Ru@Ag/AgCl-200 catalyst delivered a low output potential of 1.53 V and sustained long-term stability of 50 h at a current density of 10 mA cm −2 for water splitting. This work provides a framework for accelerated galvanostatic interaction for the controlled synthesis of Ru-based catalysts, which can be used for boosting the HER in alkaline solutions. The synthesis of core-shell Ru@Ag/AgCl catalysts via accelerating galvanostatic interactions in cathodes for dramatically boosting HER activity.